Effect of molecular weight of hyaluronic acid (HA) on viscoelasticity and particle texturing feel of HA dermal biphasic fillers. Issue 1 (December 2016) - Chun, Cheolbyong; Lee, Deuk; Kim, Jin-Tae; Kwon, Mi-Kyung; Kim, Young-Zu; Kim, Seok-Soon
Abstract Background Hyaluronic acid (HA) dermal biphasic fillers are synthesized for their efficacy in correcting aesthetic defects such as wrinkles, scars and facial contouring defects. The fillers consist of crosslinked HA microspheres suspended in a noncrosslinked HA. To extend the duration of HAs within the dermis and obtain the particle texturing feel, HAs are crosslinked to obtain the suitable mechanical properties. Results Hyaluronic acid (HA) dermal biphasic fillers are prepared by mixing the crosslinked HA microspheres and the noncrosslinked HAs. The elastic modulus of the fillers increased with raising the volume fraction of the microspheres. The mechanical properties and the particle texturing feel of the fillers made from crosslinked HA (1058 kDa) microspheres suspended in noncrosslinked HA (1368 kDa) are successfully achieved, which are adequate for the fillers. Conclusions Dermal biphasic HA fillers made from 1058 kDa exhibit suitable elastic moduli (211 to 420 Pa) and particle texturing feel (scale 7 9).